Contribution à l’étude « in vitro » du pouvoir antagoniste de Trichoderma harzianum et Trichoderma asperellum Vis-àvis d’Ascochyta sp. agent responsable de « L’anthracnose » du pois (Pisum sativum L.) - MESFEK, Souheyr; BELABASSI, Bochra (My University, 2016)
The present work focuses on the in vitro study of the effect of the antagonism of Trichoderma on Ascochyta sp., the causal agent of anthracnose peas, using two methods of direct confrontation on the culture medium and confrontation from a distance. The results we have obtained, were that direct confrontation colonies of Trichoderma with those of the pathogen Ascochyta results in inhibition and growth arrest distance of the parasite. Sporulation colonies of Ascochyta along the zone of inhibition are greatly reduced, We remark that T. asperellum is the most useful to hinder the increasment of all kinds of the tested Ascochyta. In addition, the results of indirect confrontation show a reduction in growth and sporulation of Ascochyta sp. under the action of the volatiles emitted by Trichoderma.
Keywords: antagonism; Trichoderma sp; Ascochyta sp; pea; in vitro study; direct confrontation; volatiles substances; indirect confrontation; مواد طيارة المواجهة غير المباشرة; العداء; المواجهة المباشرة; الدراسة في المختبر; البزلاء; antagonisme; substances volatiles.; Trichoderma sp.; Ascochyta sp; petit pois; étude in vitro; confrontation directe; confrontation indirecte